Cryoprotective Effect of Tara Gum on Myofibrillar Protein from Grass Carp during Frozen Storage - Xia ZHANG; Lingzhi ZHANG; Yuqi ZHANG; Juan GUO; Yuqin DING (Shipin gongye ke-ji, 2022)
To investigate the cryoprotective effect of tara gum on myofibrillar proteins, the influences of tara gum on the freezing curve of myofibrillar proteins of grass carp were studied using a commercial cryoprotectant (4% sucrose+4% sorbitol) as a control in this study. The effects of tara gum on the freezing stability of myofibrillar proteins during frozen storage (0~28 days) were investigated by assessing Ca2+-ATPase activity, sulfhydryl content, surface hydrophobicity, endogenous fluorescence spectra and water mobility. The results showed that the freezing temperature of myofibrillar proteins solution added with 1% tara gum and commercial cryoprotectant were −8.3 ℃ and −7.3 ℃, respectively, which were significantly lower than that of the control (−5.5 ℃). After 28 d of frozen storage, the Ca2+-ATPase activity, total sulfhydryl content, and active sulfhydryl content of myofibrillar proteins with the addition of 1% tara gum and commercial cryoprotectant decreased by 45.69% and 45.17%, 24.49% and 42.28%, 25.13% and 39.79%, and the surface hydrophobicity increased by 176.00% and 122.23%, respectively. The changes were significantly lower than those of the blank control. Additionally, the results of LF-NMR showed that the addition of 1% gum and commercial cryoprotectant significantly inhibited the increase of water mobility of myofibrillar protein solution after thawing. Therefore, the 1% tara gum could enhance the stability of myofibrillar proteins of grass carp during frozen storage.